2019
DOI: 10.1016/j.ecolind.2019.05.026
|View full text |Cite
|
Sign up to set email alerts
|

A general framework for quantifying the effects of land-use history on ecosystem dynamics

Abstract: Land-use legacies are important for explaining present-day ecological patterns and processes. However, an overarching approach to quantify land-use history effects on ecosystem properties is lacking, mainly due to the scarcity of high-quality, complete and detailed data on past land use. We propose a general framework for quantifying the effects of land-use history on ecosystem properties, which is applicable (i) to different ecological processes in various ecosystem types and across trophic levels; and (ii) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 73 publications
(105 reference statements)
0
5
0
Order By: Relevance
“…Second, we treat the combined land useeconomic system as a unit and study the characteristic transitions using a Hidden Markov model approach (Usher 1981, Depauw et al 2019, McClintock et al 2020. Markov chain models allow us to study the properties that result in a tipping point as an emergent phenomenon including path dependence at the pixel level (Geoghegan et al 1998) and the potential for lock-in, non-determinism, and nonunidirectional change.…”
Section: Methodsmentioning
confidence: 99%
“…Second, we treat the combined land useeconomic system as a unit and study the characteristic transitions using a Hidden Markov model approach (Usher 1981, Depauw et al 2019, McClintock et al 2020. Markov chain models allow us to study the properties that result in a tipping point as an emergent phenomenon including path dependence at the pixel level (Geoghegan et al 1998) and the potential for lock-in, non-determinism, and nonunidirectional change.…”
Section: Methodsmentioning
confidence: 99%
“…However, this level of analysis was beyond the scope of our study. Understanding past land use in the region may help explain some of the variability observed among groups, considering that current land use may not reflect past land uses ( Depauw et al, 2019 , Steel et al, 2017 ). Across the region, further examination of the interaction between epilimnetic releases of warm water from low head dams, reach-scale groundwater-surface water exchange, contributions from cold tributaries, and the effects of water withdrawals is needed to understand how these factors may influence summer thermal conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Temperate forest herb layers are slow‐changing systems (Dornelas et al, 2013; Perring et al, 2018), and understorey communities can display a delayed response to overstorey canopy and light dynamics (Plue et al, 2013). Hence, the current understorey composition might be more strongly related to past light availability (and thus past management) than to the contemporary light conditions (Depauw et al, 2019a). Ash and Barkham (1976) studied understorey composition in coppiced woodlands and found that many perennials can persist throughout the entire coppice cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, in vegetation resurvey studies, which provide a unique opportunity to estimate vegetation and environmental changes over the past decades (Kapfer et al, 2017), values of light availability at the forest floor in the past (e.g. at the time of the original survey) are typically not available, and light levels need to be estimated from stand or tree characteristics that were recorded (Depauw et al, 2019a).…”
Section: Introductionmentioning
confidence: 99%